Effects of squash leaf trichome exudates and honey on adult feeding, survival, and fecundity of the squash bug (Heteroptera: Coreidae) egg parasitoid Gryon pennsylvanicum (Hymenoptera: Scelionidae) - Nechols, James R.; Olson, D. L. (My University, 1995)
A laboratory experiment was conducted to determine whether leaf exudates could be used as a source of adult nutrition for the squash bug, Auasa tristis (De Geer), egg parasitoid, Gryon pennsylvanicum (Ashmead), and to compare adult and progeny fitness traits when female Wasps were provided with squash leaves, a standard honey diet, a combination of leaves and honey, or water only Results showed that fecundity, progeny developmental rates, and progeny survival did not differ significantly when females were exposed to different dietary sources. Adult longevity was shorter on squash leaves without honey than on leaves with honey or the honey-only diet. However, reproductive fitness was not reduced because oviposition had been completed before death of the adult females. When only water was provided, parasitoid females lived only a few days. Observations showed that squash leaves have two kinds of trichomes (hair-like and peg-like), both of which produce droplets that are fed on by both sexes of G. pennsylvanicum. Nutrient analyses revealed that exudates from the hair-like trichomes are composed predominantly of monosaccharides (mainly glucose and galactose), and that the peg-like trichomes produce glucose and some protein. Thus, these trichomes appear to serve as extrafloral nectaries and may provide an important energy source for augmentatively released G. pennsylvanicum.
Citation: Olson, D., & Nechols, J. Effects of Squash Leaf Trichome Exudates and Honey on Adult Feeding, Survival, and Fecundity of the Squash Bug (Heteroptera: Coreidae) Egg Parasitoid Gryon pennsylvanicum (Hymenoptera: Scelionidae). Environmental Entomology, 24(2), 454-458. https://doi.org/10.1093/ee/24.2.454
Keywords: Gryon pennsylvanicum; Egg parasitoid; Adult diet; Squash bug